Western Sahara's Unlearned Lessons. Issue 3 (12th September 2022) - Jett, Dennis
Abstract: The situation in the Western Sahara illustrates an unfortunate aspect of international relations: When countries pursue their national interests and ignore international principles, they can create problems that defy resolution. Such problems are often dumped in the lap of the United Nations, which frequently lacks the means to solve them. The struggle between Morocco's desire to annex the Western Sahara and the Algerian‐backed effort for it to be an independent country has led to an impasse. The United States has tried to have it both ways by making statements designed to suggest the two mutually exclusive options are possible. While this intractable dispute drags on and the possibility of renewed hostilities increases, a UN peacekeeping mission, established more than 30 years ago but that accomplishes little to nothing, continues with no end in sight.